Elaboration Tolerant Representation of Markov Decision Process via Decision-Theoretic Extension of Probabilistic Action Language pBC+. Issue 3 (23rd May 2021) - WANG, YI; LEE, JOOHYUNG
Abstract: We extend probabilistic action language pBC + with the notion of utility in decision theory. The semantics of the extended pBC + can be defined as a shorthand notation for a decision-theoretic extension of the probabilistic answer set programming language LP MLN . Alternatively, the semantics of pBC + can also be defined in terms of Markov decision process (MDP), which in turn allows for representing MDP in a succinct and elaboration tolerant way as well as leveraging an MDP solver to compute a pBC + action description. The idea led to the design of the system pbcplus2mdp, which can find an optimal policy of a pBC + action description using an MDP solver.